2019
DOI: 10.1371/journal.pone.0223730
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students and nurses’ knowledge and attitudes regarding children’s pain: A comparative cross-sectional study

Abstract: IntroductionNurses encounter children who report of pain of diverse and unknown causes in their professional work. The current study therefore assessed and compared nursing students and nurses’ knowledge and attitudes pertaining to children’s pain in the Ghanaian context. The goal of this was to have a baseline information to guide the development and implementation of the content for a sustainable educational programme (short-course) for nursing students and nurses in Ghana.MethodsBetween October and December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
(42 reference statements)
5
11
2
Order By: Relevance
“…Given the vast differences between nursing curricula and that of prehospital practitioners in South Africa, variances between the in-hospital and out-of-hospital setting and the fact that the questionnaire used was only face validated, makes direct comparison difficult and limited. The low scores obtained by the respondents in the present study are similar to those reported in studies conducted among nurses and other HCPs from various countries including the African region [45][46][47][48][49][50][51][52][53][54][55][56][57]. Studies from North America [58][59][60], Norway [61] and Australia [62] found substantially higher (72 to 79%) knowledge and attitudes scores among nurses.…”
Section: Knowledge and Attitudes Regarding Painsupporting
confidence: 83%
“…Given the vast differences between nursing curricula and that of prehospital practitioners in South Africa, variances between the in-hospital and out-of-hospital setting and the fact that the questionnaire used was only face validated, makes direct comparison difficult and limited. The low scores obtained by the respondents in the present study are similar to those reported in studies conducted among nurses and other HCPs from various countries including the African region [45][46][47][48][49][50][51][52][53][54][55][56][57]. Studies from North America [58][59][60], Norway [61] and Australia [62] found substantially higher (72 to 79%) knowledge and attitudes scores among nurses.…”
Section: Knowledge and Attitudes Regarding Painsupporting
confidence: 83%
“…The low scores obtained by the respondents in the present study are similar to those reported in studies conducted among nurses and other HCPs from various countries including the African region (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56). Studies from North America (57-59), Norway (60) and Australia (61) found substantially higher (72% to 79%) knowledge and attitudes scores among nurses.…”
Section: Knowledge and Attitudes Regarding Painsupporting
confidence: 83%
“…The low scores obtained by the respondents in the present study are similar to those reported in studies conducted among nurses and other HCPs from various countries including the African region (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57). Studies from North America (58-60), Norway (61) and Australia (62) found substantially higher (72% to 79%) knowledge and attitudes scores among nurses.…”
Section: Knowledge and Attitudes Regarding Painsupporting
confidence: 83%